Neuropsychological Perspective on Autistic Spectrum Disorder Individuals with Savant Syndrome - Muchamad Salamun Abdul Rahman; Nadia Riwu Kaho; Nadief Fikri Jatmiko; Gian Baringin Noach; Supra Wimbarti; Zulfikri Khakim (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The high prevalence of individuals with ASD has shifted the focus of research toward exploring strengths rather than weaknesses, one of which is the phenomenon of savant syndrome, which is most commonly observed in individuals with ASD. However, studies specifically examining the neuropsychological basis of individuals with ASD and savant syndrome remain limited. Therefore, this study aims to explore the characteristics of brain structure and cognitive function in individuals with ASD and savant syndrome using the narrative literature review method. The literature review findings indicate that individuals with ASD and savant syndrome exhibit distinct brain structures and specific cognitive functions that differentiate them from both individuals with ASD without savant syndrome and the general population. These findings provide new insights into the relationship between neuropsychological aspects and the extraordinary abilities possessed by individuals with savant syndrome. The implications of this study serve as a scientific foundation for developing intervention strategies and educational approaches that are better suited to the unique needs and potential of individuals with ASD and savant syndrome. Prevalensi individu dengan ASD yang tinggi telah menggeser arah penelitian untuk lebih menitikberatkan pada kekuatan daripada kelemahan, salah satunya adalah fenomena savant syndrome yang paling banyak dialami oleh individu dengan ASD. Meskipun demikian, penelitian yang secara spesifik mengkaji dasar neuropsikologis individu ASD dengan savant syndrome masih tergolong terbatas. Oleh karena itu, penelitian ini bertujuan untuk mengungkap karakteristik struktur otak dan fungsi kognitif individu ASD dengan savant syndrome melalui metode narrative literature review. Hasil dari tinjauan literatur menunjukkan bahwa individu ASD dengan savant syndrome memiliki pola struktur otak yang khas serta fungsi kognitif tertentu yang membedakan mereka dari individu ASD tanpa savant syndrome maupun populasi umum. Temuan ini memberikan wawasan baru mengenai keterkaitan antara aspek neuropsikologis dan kemampuan luar biasa yang dimiliki oleh individu dengan savant syndrome. Implikasi dari penelitian ini adalah memberikan landasan ilmiah yang dapat digunakan dalam pengembangan strategi intervensi dan pendekatan edukatif yang lebih sesuai dengan kebutuhan serta potensi unik individu ASD dengan savant syndrome.